Psychometric Properties and Factor Structure of the Short Form of the Affective Lability Scale in Adult Patients With ADHD. Issue 10 (August 2019) - Weibel, Sébastien; Micoulaud-Franchi, Jean-Arthur; Brandejsky, Laura; Lopez, Régis; Prada, Paco; Nicastro, Rosetta; Ardu, Stefano; Dayer, Alexandre; Lançon, Christophe; Perroud, Nader
Objective: Affective lability is an important dimension of adult ADHD, associated with marked impairments and worse outcomes. A valid and quick tool to measure affective lability may therefore be of interest.Method: In 187 adult ADHD patients, we explored psychometric properties of the Affective Lability Scale–Short Form (ALS-18 items). We analyzed the construct validity and the external validity of the scale. Patients were compared with 48 healthy adult controls.Results: The three-factor structure of the ALS-18 presented a good fit and a good internal consistency. The correlations between the ALS-18 and ADHD symptoms and other psychological dimensions were, respectively, low and moderate. ALS-18 scores were higher in patients than in healthy adults.Conclusion: ALS-18 showed good psychometric properties in ADHD adult patients, allowing us to recommend the implementation of ALS-18 in assessing affective lability for clinical and research purposes. Use of ALS-18 should improve the clinical assessment of affective lability in adult ADHD patients.